Derivational Suffixes in Joe Biden’s Instagram Captions - Sukawati, Anak Agung Ngurah; Ni Putu Cahyani Putri Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study's focus was to analyze Joe Biden's Instagram captions. The aim was to determine the derivational suffixes' types by using a theory proposed by Katamba (1993). The method of descriptive qualitative is used to represent the types of suffixes. The observation method was utilized by reading Instagram captions. Then in collecting data, a note-taking technique was applied by writing down the words with suffixes that belonged to the topic of the study. According to Katamba (1993), there were eleven types of derivational suffixes. Meanwhile, this study found nine types of suffixes because two types, such as -less and -full were not found. There was a total of 42 data with nine types of suffixes found. The data consist of suffixes; two -hood, one -ship, five -ness, five -ity, five -ment, one-ic, eight -al, four -er, eleven -ly. Based on the analysis, nine types of suffixes were found, and the most data was by suffix -ly, whereas the lowest data was by the suffix -ship and -ic.